Investimentos em Ativos Imobilizados Para Instalação de Usina de Reciclagem de Resíduos de Construção Civil de Médio Porte da Zona Leste de São Paulo - João Alexandre Paschoalin Filho (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
New tools for management of waste generated by the Civil Construction have attracted attention and been the subject of several surveys conducted by this industry. Among these, recycling can be highlighted, as it provides the reduction of discarded volumes and the need to purchase natural raw material, resulting in significant economic gains and reduced environmental impact. This paper estimates the investments necessary to implement a medium-sized waste recycling plant to be loca- ted at east side of the city of São Paulo. This paper also brings comparisons between market prices of natural aggregates and recycled wastes produced by recycling plants and mines located in the cities of São Paulo, Guarulhos and Osasco, in order to establish a comparison between the two. To this end, this qualitative exploratory study presents a case study, in which they were technical visits to same-sized mills and quarries, desk research and interviews with managers in order to identify items essential for implementation of the plant under study. The results showed that the demand in the East Zone of São Paulo presents regarding the recycling of construction waste, confirming the viability of the studied plant. It was also observed that the market prices of recycled aggregates in the surveyed plants were lower than natural aggregates, demonstrating the economic feasibility of its use.